2009
DOI: 10.1021/jf8026765
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Reaction Rates of Various Antioxidants with ABTS Radical Cation

Abstract: The reaction rates of several aminothiol, amidothiol, and phenolic antioxidants with ABTS radical cation were measured. Most compounds had half-lives of less than one minute. However several compounds had considerably longer half-lives. Aminothiol derivatives lacking a free thiol group, such as amifostine and RibCys, displayed longer half-lives. Reaction of these compounds with the ABTS radical cation displayed first order kinetic behavior. Of the phenolic compounds studied, chlorogenic acid and caffeic acid h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(116 citation statements)
references
References 17 publications
10
105
0
1
Order By: Relevance
“…Trolox is a water-soluble analogue for vitamin E and is used frequently as the reference antioxidant for the ABTS antioxidant assay [45]. Past research showed the antioxidant activity trolox was unaffected by pH values below 10 which is consistent with results in Figure 2.…”
Section: Effect Of Ph On Pure Antioxidantssupporting
confidence: 83%
“…Trolox is a water-soluble analogue for vitamin E and is used frequently as the reference antioxidant for the ABTS antioxidant assay [45]. Past research showed the antioxidant activity trolox was unaffected by pH values below 10 which is consistent with results in Figure 2.…”
Section: Effect Of Ph On Pure Antioxidantssupporting
confidence: 83%
“…12,[28][29][30][31] The rate constants however depend greatly on the type of antioxidant and the solvent composition. 3,12 In the present section we have not focused on the kinetics of the fast phases but rather on the amplitude that is directly proportional to the determined AOP, in order to show how incubation time influences its value.…”
Section: Aop Of Selected Drinks and Food Supplements Obtained By Dmentioning
confidence: 99%
“…It is assumed that protein activity of rapid reducing centers is primarily associated with cysteine (Cys) SH-group which is not involved into the formation of disulfide bounds [13]. Albumin molecule has one free Cys however the analysis of first derivatives of protein absorption spectra testifies against increasing of protein chromophore accessibility to the solvent (Fig.…”
Section: Resultsmentioning
confidence: 99%